Shumaker, David: The Embedded Librarian: Innovative Strategies for Taking Knowledge Where It’s Needed. Medford: Information Today, 2012 - Thalmair, Rene (Mitteilungen der Vereinigung Österreichischer Bibliothekarinnen und Bibliothekare, 2019)
Rezension von "Shumaker, David: The Embedded Librarian: Innovative Strategies for Taking Knowledge Where It's Needed. Medford: Information Today, 2012. – XVII, 212 S. ISBN: 9781573874526"